Case Report: Family Curse: An SCN5A Mutation, c.611C>A, p.A204E Associated With a Family History of Dilated Cardiomyopathy and Arrhythmia - Huang, Wen; Xu, Rui; Gao, Ning; Wu, Xia; Wen, Cong (Frontiers in Cardiovascular Medicine, 2022)
Objective: To study the clinical characteristics and gene mutation of a family with dilated cardiomyopathy. Methods: The relevant clinical data of 15 individuals from the same family were collected, and Whole Exome Sequencing (WES) was performed for 8 persons. Results: The clinical manifestations of the family members were varied, the proband(female) began to have disease when she was adults, while the proband's children began to have disease when they were minors. WES showed the family with dilated cardiomyopathy with a c.611C>A，p.A204E SCN5A mutation. The proband's childhood-onset son had multiple gene mutations, and the combined mutation of multiple genes may be the cause of early onset and severe illness in the child. Conclusion: The clinical manifestations of the family with dilated cardiomyopathy with a c.611C>A，p.A204E SCN5A mutation are diverse, and this has only been reported in individual cases but not in families.